2018
DOI: 10.1159/000495866
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analyses of the Role of miR-21 in Acute Pancreatitis

Abstract: Background/Aims: Our previous study demonstrated that a deficiency of microRNA 21 (miR-21) protects mice from acute pancreatitis, yet the underlying molecular networks associated with miR-21 in pancreatitis and pancreatitis-associated lung injury remain unexplored. Methods: We used next generation sequencing to analyze gene expression profiles of pancreatic tissues from wild-type (WT) and miR-21 knockout (KO) mice treated with caerulein by using a 1-day treatment protocol. The Database for Annotation, Visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Additionally, the overexpression of miR-21-3p in acinar cells inhibited apoptosis (Wang et al, 2018), which nullifies the protective effects of apoptosis for preventing leakage of necrotic substances and limiting inflammation (Najenson et al, 2018), and also promotes necroptosis of pancreatic acinar cells (Ma et al, 2015), thereby aggravating the injury of pancreatic tissues. Additionally, it was confirmed by several studies that deficiency of miR-21 in mice contributed to amelioration of pancreatic injury during AP (Ma et al, 2015;Li et al, 2018a). However, the upstream regulatory factors of miR-21 involved in SAP are not known yet.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, the overexpression of miR-21-3p in acinar cells inhibited apoptosis (Wang et al, 2018), which nullifies the protective effects of apoptosis for preventing leakage of necrotic substances and limiting inflammation (Najenson et al, 2018), and also promotes necroptosis of pancreatic acinar cells (Ma et al, 2015), thereby aggravating the injury of pancreatic tissues. Additionally, it was confirmed by several studies that deficiency of miR-21 in mice contributed to amelioration of pancreatic injury during AP (Ma et al, 2015;Li et al, 2018a). However, the upstream regulatory factors of miR-21 involved in SAP are not known yet.…”
Section: Discussionmentioning
confidence: 89%
“…A body of evidence indicates that altered expression of miRNAs is implicated in the pathogenesis of AP in animal models and human specimens (Xiang et al, 2017;Yang et al, 2019). Furthermore, functional studies also confirm that knockdown of certain miRNAs (e.g., miR-21) can be conducive to the reduction of damage caused by SAP (Ma et al, 2015;Li et al, 2018a). Although the roles of miRNAs have been well characterized, the precise mechanisms of miRNAs in SAP remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed that the decrease of HMGB1 in circulation can effectively alleviate the ALI caused by AP (Jo et al, ; Luan et al, ). The expression of HMGB1 in both immune cells and circulation is lower in AP mice with miR‐21 deficiency and the ALI is milder as well (Li et al, ). Supporting the data, miR‐21‐3p is upregulated in lung tissue of AP rats, which aggravates ALI and impairs lung oxygenation function (T. Wang et al, ).…”
Section: Mirnas and Ap Pathogenesismentioning
confidence: 99%
“…In recent years, a number of studies have reported that miRs are closely related to the occurrence and development of AP (11,27); however, the role of miRs in HTGAP has not been extensively reported. In the present study, RT-qPCR results suggested that the level of miR-372 in the serum of patients with HTGAP was significantly increased compared with patients who did not have HTGAP, indicating that the expression of miR-372 was abnormally high in patients with HTGAP.…”
Section: Discussionmentioning
confidence: 99%